2007
DOI: 10.1017/s0020859006002793
|View full text |Cite
|
Sign up to set email alerts
|

Migration and World History: Reaching a New Frontier

Abstract: Migration history has made some major leaps forward in the last fifteen years or so. An important contribution was Leslie Page Moch's Moving Europeans, published in 1992, in which she weaves the latest insights in migration history into the general social and economic history of western Europe. Using Charles Tilly's typology of migration patterns and his ideas on the process of proletarianization since the sixteenth century, Moch skilfully integrates the experience of human mobility in the history of urbanizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In Asia there were similar developments, with large numbers of migrants flocking to centres of capital in Northern and South-East Asia (McKeown 2004;Manning 2005;Lucassen 2007). At the same time, however, Asian migrants were excluded as much as possible from the Atlantic world and white settler colonies, creating a global, racially motivated migration regime which aimed at keeping Asians in Asia, except for relatively small numbers of indentured migrant workers, mostly in the Caribbean.…”
Section: Illegality From a Historical Perspectivementioning
confidence: 99%
“…In Asia there were similar developments, with large numbers of migrants flocking to centres of capital in Northern and South-East Asia (McKeown 2004;Manning 2005;Lucassen 2007). At the same time, however, Asian migrants were excluded as much as possible from the Atlantic world and white settler colonies, creating a global, racially motivated migration regime which aimed at keeping Asians in Asia, except for relatively small numbers of indentured migrant workers, mostly in the Caribbean.…”
Section: Illegality From a Historical Perspectivementioning
confidence: 99%
“…African slavery, Asian indentured servitude and the migration of millions of European peasants who moved to agrarian colonies are part of the first phase in the world market for labour power. Although these migration stories have hardly been studied together, scholars working in the field of historical migration studies have recently shown that they have more similarities than previously assumed (Lucassen 2007). In particular, McKeown (2004) has observed that transatlantic migration and Asian migration in the nineteenth century are not only comparable in volume, but respond to the ups and downs of the same global economic structure.…”
Section: Marketsmentioning
confidence: 99%
“…In doing this, we hope to bring together historical and contemporary research on migration, thus responding to the calls of scholars such as Bade (2003) and Lucassen (2007) to see migration as an important and intrinsic part of Europe's history. Rather than privileging some types of migration over others (e.g.…”
Section: Introductionmentioning
confidence: 99%